The books of Samuel the sovereignty of God illustrated in the lives of Samuel, Saul and David - Barber, Cyril J. (Neptune, NJ Loizeaux, 1994)
Contents : v.1 : a devotional commentary on first Samuel. Includes bibliographical references and indexes.
Keywords: Bible. O.T. Samuel, 1st -- commentaries